1972
DOI: 10.1084/jem.135.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Marrow-Derived and Thymus-Derived Small Lymphocytes in the Lymphoid Tissue and Thoracic Duct Lymph of Normal Rats

Abstract: All the specific radiosensitive cells required for the induction and expression of the primary antibody response to sheep erythrocytes in the rat are normally present among the small lymphocytes in thoracic duct lymph (1, 2). Experiments with radiation chimeras have now made it clear that the activity of thoracic duct cells in this response is due to the presence in rat lymph of two populations of small lymphocytes, one derived from the thymus (T lymphocytes) 1 and the other derived from the bone marrow withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(85 citation statements)
references
References 16 publications
4
80
0
1
Order By: Relevance
“…The origin of these marginal zone lymphocytes is not known, but there is evidence for two possible sources. Howard et al (11) and Sprent (18) have shown that B lymphocytes continuously recirculate from the blood to the follicular region of splenic white pulp. The route followed has not yet been determined; it is conceivable, however, that it lies along a pathway that includes blood sinuses in the marginal zone.…”
Section: Simplified Protocol For Preparing Antisera Specific Formentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of these marginal zone lymphocytes is not known, but there is evidence for two possible sources. Howard et al (11) and Sprent (18) have shown that B lymphocytes continuously recirculate from the blood to the follicular region of splenic white pulp. The route followed has not yet been determined; it is conceivable, however, that it lies along a pathway that includes blood sinuses in the marginal zone.…”
Section: Simplified Protocol For Preparing Antisera Specific Formentioning
confidence: 99%
“…B lymphocytes have been distinguished from T lymphocytes by their buoyant density, decreased rate of incorporation of RNA precursors, and propensity to migrate to the "thymus-.ndependent" areas of peripheral lymphoid tissue (10,11). 1…”
mentioning
confidence: 99%
“…All macrophages in the GC have large, densely staining, phagocytic inclusions called tingible bodies (T). The mantle contains many small lymphocytes (SL), probably recirculating B cells (12,18). Macrophages (MAC) are present, though only a minority contain tingible bodies.…”
Section: Anatomy Of Fdc' Smentioning
confidence: 99%
“…1 and 11). The latter consisted mainly of small lymphocytes (probably recirculating B cells [12,18]), as well as scattered lymphoblasts, macrophages, plasma cells, and cells which we termed FDC's. The mantle and GC proper together were referred to as a secondary follicle.…”
Section: Microscopymentioning
confidence: 99%
“…The migrations of lymphocytes were specific to subtypes and microenvironment (Ford and Simmomds 1972 ;Howard et al 1972 ;Haynes and Fauci 1978) and were influenced by steroid, antigen, and genetic factors (Ford 1972;Moorhaed and Claman 1972;Bona 1979). It was suggested that the circulating lymphocytes were more adherent to the target tissue ; this binding between lymphocytes and target tissue thus controls the migratory pattern of lymphocytes from peripheral blood to the organized lymphoid organs such as lymph nodes (Jalkanen et al 1986).…”
Section: Con a Indexmentioning
confidence: 99%